Institutional communication: problematic concept and challenges of adoption - Lamine, Imane; Othmani, Karima (Journal of Human Sciences, 2022)
The main objective of this work is to determine the existing overlap between the two concepts: institutional communication and other communication activities carried out in the company, such as public relations, marketing communication and institutional marketing. This is achieved by identifying the similarities and the differences with the aim of designating rules that could simplify the differentiation between these two concepts. In the literature related to this subject, it can be seen that this overlap is mainly due to the existence of many similarities between institutional communication and the other concepts which are mainly attached to: the practice, the preservation of the reputation, the construction of external and internal relations with the public and the reinforcement of a positive image of the institution which guarantees its survival and its competition in its environment. Regarding the points of difference, the question of communication was the separator between the concept of institutional communication and the rest of the concepts.